Cooperative DNA Compaction by Ternary Supramolecular Complex with Cucurbituril/Cyclodextrin Pair. Issue 4 (4th April 2016) - Zhang, Xu‐Jie; Zhang, Ying‐Ming; Wang, Ze; Chen , Yong; Liu , Yu
Abstract: DNA condensation plays a vital role in regulating cell life. Herein, we report a supramolecular complex with synergistic and specific DNA‐condensing ability, which is achieved by the cucurbituril‐induced conformational change and p K a shift in aqueous solution. The complexation with cucurbit[6]uril can drive the side chain of 1, 6‐diaminohexane out of β ‐cyclodextrin's cavity to increase the molecular rigidity and meanwhile, the supramolecular p K a shift from 10.81 to 12.15 can ensure the amount of positive charges, which facilitate the close contact with DNA. By benefiting from β ‐cyclodextrin's hydrophobic cavity, the binary cucurbituril–cyclodextrin complex can be further decorated with anthryl adamantane. Furthermore, it is demonstrated that the resultant ternary assembly originating from the integration of cucurbituril–cyclodextrin macrocyclic pair with the protonated ammonium chain and π ‐conjugated anthryl adamantane can efficiently bind to the DNA backbones, thus resulting in the DNA morphological transition from loose clews to compact nanoparticles. Thus, this supramolecular complex may have powerful potential as compacting agent for nucleic acids in non‐viral gene delivery. Abstract : A ternary assembly constructed from 1, 6‐diamine‐modified β ‐CD, cucurbit[6]uril and anthryl adamantane can synergistically condense DNA into particulate structures, which is promoted by the cucurbituril‐induced conformational change and supramolecular p K a shift in DNA groove binding process.